Chemical characterization of fructooligosaccharides, inulin and structurally diverse polysaccharides from chamomile tea. (15th June 2019) - Chaves, Pedro Felipe P.; Iacomini, Marcello; Cordeiro, Lucimara M.C.
Highlights: Polysaccharides from the chamomile tea were purified and characterized. Inulin, HM homogalacturonan and a type II arabinogalactan were obtained. Fructooligosaccharides ranging from GF2 ( m / z 543) to GF10 ( m / z 1839) were also present. Chamomile is a source of structurally diverse dietary fibers. Chamomile tea polysaccharides could have potential prebiotic function. Abstract: Chamomile is one of most known species of medicinal plants. It has valuable pharmacological properties that produce positive effects in many therapeutical uses. Some of these properties are attributed to the presence of secondary metabolites but is already known that primary metabolites can also produce positive effects. In this study we elucidate the fine chemical structure of polysaccharides present in the infusion of chamomile flower chapters. After ethanolic precipitation, polysaccharides were obtained from the tea (fraction MRW, 3.2% yield), purified and characterized as an inulin type fructan, a highly methyl esterified and acetylated homogalacturonan (DE = 87% and DA = 19%), and a type II arabinogalactan. From ethanolic supernatant (20.2% yield), fructooligosaccharides (FOS) ranging from GF2 ( m / z 543) to GF10 ( m / z 1839) were detected. Inulin and FOS are well-established prebiotics, as well as the pectic polysaccharides. Thus, chamomile could be a source of structurally diverse dietary fibers with potential prebiotic, gastrointestinal and immunological functions.